PENGARUH MANAJEMEN HUBUNGAN PELANGGAN DAN REPUTASI PERUSAHAAN TERHADAP RETENSI PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Bengkel Alex Ac Mobil Semarang) - Bagas Amanda Putra; Susilo Toto Rahardjo (Diponegoro Journal of Management, 2022)
Number of motorized vehicle users certainly cannot be separated from motor vehicle maintenance activities, especially four-wheeled vehicles. The tight competition in the workshop industry and the deteriorating economic conditions due to Covid-19 have reduced the potential revenue for the workshop industry in the country. One of the workshops operating in Indonesia is Alex AC Mobil, located in Semarang, Central Java, the province with the largest number of motorized vehicle users in Indonesia. Alex AC Mobil has been operating for almost 15 years with two branches operating on Jl. Supryadi No.23 and Jl. Kedungmundu 101 Karanggawang Baru. With the decrease in income in the workshop industry, it is expected that every workshop must be able to maintain every customer it has, this is called Retensi pelanggan Customer Retention. This study aims to determine the effects that arise through Customer Relationship Management, Company Reputation, Customer Satisfaction, Customer Retention in order to retain Alex AC Mobil's customers. The data collection method used in this study is convenience sampling, which is sampling by taking samples from a close part of the population. Then this study was tested with a total of 198 samples obtained from questionnaires and directed specifically to customers who have used the services of Alex AC Mobil. The data obtained were processed using SEM analysis with the help of AMOS software to test 5 hypotheses. The results of this study indicate that Customer Relationship Management, Company Reputation, Customer Satisfaction have a positive and significant effect on Customer Retention.